ATM Mutations Benefit Bladder Cancer Patients Treated With Immune Checkpoint Inhibitors by Acting on the Tumor Immune Microenvironment - Yi, Ruibin; Lin, Anqi; Cao, Manming; Xu, Abai; Luo, Peng; Zhang, Jian (Frontiers in Genetics, 2020)
Immune checkpoint inhibitors (ICIs) have shown promising results in bladder cancer (BC). However, only some patients respond to ICIs. DNA repair defects (DDR) play an important role in the therapeutic response of bladder cancer. Therefore, we aimed to elucidate the association between ICIs in bladder cancer and ataxia telangiectasia mutated (ATM), a core component of the DNA repair system. From a collected immunotherapy cohort (n=215) and The Cancer Genome Atlas (TCGA)-Bladder cancer cohort, which were both retrieved from publicly available resources, we performed a series of analyses to evaluate the prognostic value and potential mechanism of ATM in bladder cancer immunotherapy. We found that ATM-mutant (ATM-MT) bladder cancer patients derived greater benefit from ICIs (overall survival [OS], hazard ratio [HR] = 0.28, [95% confidence interval (CI), 0.16 to 0.51], P= 0.007) and showed a higher mutation load (P<0.05) and immunogenicity (P<0.05) than ATM-wild-type (ATM-WT) patients. The immune inflammatory response to antigenic stimulation, the regulation of the IFN pathway and the macrophage activation pathway were significantly enriched in the ATM-MT group (NES>1, P<0.05), while insulin-like growth factor receptor signaling pathways and vasculogenesis were significantly downregulated (NES<-1, P<0.05). ATM mutation significantly upregulated the number of DNA damage repair pathway gene mutations (P<0.05). ATM mutations resulted in increased bladder cancer sensitivity to 29 drugs (P<0.05), including cisplatin and BMS-536924, an IGF-1R inhibitor. Our results demonstrate the importance of ATM as a prognostic signature in bladder cancer and reveal that ATM may impact the effects of ICIs by acting on the tumor immune microenvironment.